Pairing books [feature article] - Livingston, Nancy (2000)
Pairing Books by Nancy Livingston Associate Professor Emeritus and Lillian H. Heil Professor Emeritus Brigham Young University Note: Complete bibliographic information on books mentioned in this article is found on pages three and four. Those familiar with the saying “Truth is stranger than fiction” can add another truth and fiction saying to their list. Fact enriches fiction and fiction makes fact memorable. Think about it. Facts enrich fiction by providing information about such things as history, places, scientific concepts, or people. Adding this information enriches the story because the reader becomes more familiar with facts used in the story. On the other hand, not knowing some facts may raise questions in the reader’s mind that could be found in a factual book. For example: Can an animal act that way? Does the story portray history accurately? What is the appearance of the location of the story? Fiction makes historical events come to life and paints word pictures of animals, places, and things within the context of an interesting story. Why not use them together to enrich and make learning more memorable for young readers? For Utah parents, teachers, and librarians, the new state social studies curriculum provides an opportunity to try this idea. After a five-year review of the old curriculum, the new theme is to make global connections prior to sixth grade. Kindergartners learning about small communities will compare Utah’s and Antarctica’s seasons and animals. Into the Ice: The Story of Arctic Exploration is a good introduction to the arctic. Antarctica, by Helen Cowcher, shows wonderful informational pictures of penguins in Antarctica. Antarctic Antics: A Book of Penguin Poems puts information and action into poetic form. One caution when pairing a fiction book with nonfiction is a title alone will not indicate how well the two books will pair with each other. For example, Tacky the Penguin, a fictional book, is too far-fetched and fantastic to be enriched by an informational book about penguins. First graders will make connections between their own neighborhoods and neighborhoods in Australia. Useful books about Australia include Kangaroos and Koalas: What They Have in Common and Look What Came From Australia. These could be paired with the story of Koala Lou. Second graders learning about how communities change over time will explore the community of Oueslessebougou in Mali, Africa, where the deserts are similar to those in Southern Utah. Rattlesnake Dance: True Tales, Mysteries, and Rattlesnake Ceremonies, a factual book about desert animals, could be paired with Jim Arnosky’s playful picture book also entitled Rattlesnake Dance. Third graders will be comparing Incas of South America to Indians of North America. There are few fiction or informational books about North or South American Indians suitable for third grade, but here are some possibilities. Russell Freedman’s Children of the Wild West contains a well-written chapter about the Indians of North America. Chet Cunningham has written a short biography of Crazy Horse, but it may be too difficult for most third graders. Powwow is a wonderful full-color photo essay giving a real feel for the exuberant Indian celebration. Children’s Press has published a set of nine books on American Indians, including one on families, festivals, foods, and games, as well as books about Pueblos, Shawnees, Utes, Wampanoags and Zunis. Inca Town and Lost Treasure of the Inca could be paired with these books. Other books about the Incas include Tim Wood’s picture book The Incas, and Children of the Incas, which includes photographs of the Peruvian Indians of today. Teachers might use the informational books available to set the stage for an activity in which children write fictional stories about the Indians in North and South America. Fourth graders studying Utah will also study Asia, because there are several connections between Asia and Utah. Chinese immigrants helped build the railroad, and citizens of Japanese ancestry were sent to internment camps in Utah durin g World War II. Some factual books that relate to China are Asian-Americans in the Old West and Henry Pluckrose’s China. A fictional book from China is Lon po po: A Red-Riding Hood Tale from China. Fourth graders might also explore the impact of the gold rush on the settlement of the West in the informational book The Great American Gold Rush, and the fictional books Orphan Runaways and Boom Town. Gold Fever: Tales from the California Gold Rush is based on journals and quotes from people who participated in the gold rush and would make another excellent informational book. Fifth graders will study Canada and Mexico while learning about United States history and government. The factual book Rio Grande: From the Rocky Mountains to the Gulf of Mexico can be paired with Sherry Garland’s poetic approach in Voices of the Alamo. Rio Grande Stories, a fictional book that sounds like history, could be used as a springboard for students to collect stories of the past from people in their own community. Another topic is the westward exploration. The Incredible Journey of Lewis and Clark could be paired with a fictional account, such as Joseph Bruchac’s Sacajawea: The Story of Bird Woman and the Lewis and Clark Expedition, written as if it were Sacajawea’s journal. The fictional book The Bunyans and the informational book entitled Bryce Canyon National Park could spark a study of geography. Students could do reports on all the spots visited by the Bunyans. Sixth graders will focus on ancient cultures, including Greece, Rome, and Egypt. Factual books that could arouse interest include the Usborne Time Traveller Books. Rome and the Romans could be paired with The Eagle of the Ninth, a historical fiction novel. Other Usborne books include Pharaohs and Pyramids and The Young Scientist Book of Archaeology, a book about discovering the past through science and technology. The Riddle of the Rosetta Stone would be useful in the study of ancient cultures and could be paired with the new picture book Seeker of Knowledge: the Man Who Deciphered Egyptian Hieroglyphs. Diane Stanley and Peter Vennema’s biography of Cleopatra could also be used in the study of Egypt. For the study of Greece, Paul Fleishman’s collection of myths, Dateline Troy, could be paired with a factual book on ancient Greece, such as How Would You Survive as An Ancient Greek? Adults interested in sharing books with young readers can pair fiction and informational books on topics other than those suggested in the new Utah curriculum for social studies. A possibility for older grades is using the factual book Killer Whale, with Moby Dick. This could even be adapted by using Allan Drummond’s picture book version of Moby Dick. Possibilities for younger grades include books about water. Jonathan London’s Puddles can be used with the informative Water Book. (The use of McPhail’s The Puddle is not advised because it does not talk about water.) Another topic for younger grades is city markets with the fictional Peppe, the Lamplighter, paired with Market, the Storyteller, and Touch and Go Travels of a Children’s Book Illustrator. Tornado, by Betsy Byars, could be used as an appetizer to Seymour Simon’s Tornadoes. The fictional ‘Gator Aid could be paired with Jim Arnosky’s All About Alligators. As more books came to mind, the idea was suggested that book pairing, whether it were two fiction books, two informational books, or a combination of both, would be a useful feature in each issue of Children’s Book and Play Review. Look for other book pairs in this issue and those that follow. Another source to look for book pairs and teaching strategies for comparing fact and fiction can be found in Deanne Camp’s article “It Takes Two: Teaching Twin Texts of Fact and Fiction,” in The Reading Teacher, Volume 53, No. 5, February 2000 on page 400. Start enriching the reading of young people by suggesting pairs of books on the same topic. Remember that facts enrich fiction, and fiction makes facts memo 6 p. Children's Book and Play Review, November / December 2000